Historical and Pedagogical Source and Truth Identification in the Historical and Pedagogical Science (Thoughts in the Light of the Jerzy Topolski’s Views) - Mykola Haliv (Pedagogical Discourse, 2013)
The author, based on the views of prominent Polish historian and philosopher of history Jerzy Topolskі (1928 – 1998), analyzes and reflects on the problem of historical and educational source as part of the knowledge of the past. Pointing to relativity of the sources, the author focuses on the interpretive possibilities of the researchers, working with sources, and thus on the factor of construction of historical and pedagogical narratives. Therefore the author denies the relevance of classical theory of truth for the history of pedagogy, proposing instead the concept of consensus as a way of understanding scientific truth.